Triple-Bead Mixed Amphetamine Salts (SHP465) in Adults With ADHD: Results of a Phase 3, Double-Blind, Randomized, Forced-Dose Trial. Issue 3 (February 2020) - Frick, Glen; Yan, Brian; Adler, Lenard A.
Objective: Evaluate the efficacy and tolerability of triple-bead mixed amphetamine salts (MAS) in ADHD.Method: Adults with ADHD Rating Scale IV (ADHD-RS-IV) total scores ≥32 were randomized to 6 weeks of triple-bead MAS (25, 50, or 75 mg) or placebo. The primary endpoint was ADHD-RS-IV total score change from baseline at end of study (EOS).Results: Least squares mean (95% confidence interval [CI]) treatment differences for ADHD-RS-IV total score changes from baseline to EOS significantly favored triple-bead MAS (all doses combined: −10.6 [−13.2, −8.0]; p < .0001); there were no significant differences between triple-bead MAS dosages. The most frequently reported TEAEs with triple-bead MAS (all doses combined) included insomnia, decreased appetite, and dry mouth. Mean ± SD pulse and systolic blood pressure increases at EOS were 3.5 ± 10.33 bpm and 0.3 ± 10.48 mmHg with triple-bead MAS (all doses combined).Conclusion: Triple-bead MAS significantly reduced adult ADHD symptoms; the safety profile was consistent with previous triple-bead MAS studies.